Post-COVID-19 syndrome - Vasantha Kamath; R Anand; Buvana Radhakrishnan; Kushal Markanday (Wolters Kluwer Medknow Publications, 2023)
Severe acute respiratory syndrome-CoV-2 infection has been known to cause an array of chronic consequences, most of which are yet to be studied in detail. These presentations are due to direct invasion of the tissues by the virus or other factors such as immune response to the virus. These sequelae affect the patient's quality of life implicating the importance of follow-up care in all coronavirus disease-2019 (COVID-19) patients and changing the definition of "post-COVID-19 recovery." Adequate preparedness for post-COVID consequences with adequate health care is need of the hour. This also warrants for the patients' awareness, stressing upon the importance of educating the general public about keeping a watch for certain symptoms. Regular screening procedures may also aid in timely prevention, recognition, and management hence reducing morbidity and mortality in the post-COVID phase.